Ask a question


how to solve the quadratic function step-by-step

1 Answer by Expert Tutors

Tutors, sign in to answer this question.
Daniel E. | Mathematics Made EasyMathematics Made Easy
4.9 4.9 (15 lesson ratings) (15)
first set it equal to zero, so we have 6x2-2x+1=0.
The quadratic equation tells us that x=(-b+-(b2-4ac).5)/2a. 
Where a is the coefficient in front of the x2, b is the coefficient in front of the x, and c is the constant.
Raising something to the .5 power is the same as taking the square root of that number.
So we get x=(2+-(4-4(6)(1)).5)/12=(2+-(-20).5)/12=(2+-(-4).5(5).5)/12=(2+-(2i)(5).5)/12
=(1+(5).5i)/6 and (1-(5).5i)/6.
Where i=(-1).5 which is an imaginary number used in complex analysis.